(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
Working on speech processes in students with hearing impairments is one of the main tasks of the special education system. The mother tongue textbook program, which is carried out in the process of special education, plays a large role in solving this issue. This article will talk about the direction of speech development of students with hearing problems and the possibilities of native language lessons in the process.